(untitled) (Proceedings of the International Conference on Future of Education, 2022)
The civil Service Commission Republic of the Philippines’ tagline is to convert every public employee into a heroic public servant and its constitutional mandate is to promote morale, efficiency, integrity, responsiveness, progressiveness, and courtesy in the Civil Service. Now, to begin these goals, every public employee has to pass the examination professionalizing mandate known as the Civil Service Examination (CSE). However, the problem exists if the employees are in the service for a long time but have the difficulty passing the exam, hence, the City College of Calamba, one of the city governments’ arms in community development, launched its very first “CCC Oplan Kalinga” catering a free 6-week review to registered-examinees for April 2022 schedule exam. The project primarily aims to help the examinees (employees) to refresh their courses to align with the coverage of the exam. From the review, the VPEL office formulated a study in determining if there is a significant difference in the diagnostic and post-test results of the review and test what underlying factor may affect the actual examination according to profile. The study used a pre-posttest design, reviewers who completed the training was 89, and improvement in the performance was evident via paired t-test at a p-value = 0.000. Moreover, among the three tested factors, using a two-way multivariate analysis of variance (Factorial MANOVA) only the civil status has a significant difference in their CSE post-test results at a p-value of 0.015. Also, with a significant interaction between civil status and age bracket at a p-value of 0.047. In other words, there are no significant differences in the mean scores according to age bracket alone but will be significant if the two factors together were considered such as the civil status and age bracket. The project became successful since the difference in tests was evident and hence recommended having a continuity CSE review program. Moreover, the scores will be may be used again to further study after the release of the actual CSE results who took the review.